Pengaruh Entrepreneurship Education dan Entrepreneurial Self-Efficacy Terhadap Entrepreneurial Intention dengan Dimoderasi oleh Gender (Studi Kasus Mahasiswa FEB Unisma Angkatan 2020) - Purbawati, Cindy; Diana, Nur; Afifudin, Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to determine the influence of entrepreneurial education and entrepreneurial self-confidence on entrepreneurial intentions which is moderated by gender. The respondents used were 100 FEB UNISMA students Class of 2020. By referring to the data collected and the hypothesis analysis that has been carried out, it can be concluded that, the entrepreneurial education variable has a negative influence on entrepreneurial intentions. The entrepreneurial self-confidence variable has a significant positive influence on entrepreneurial intentions. The gender variable has a negative influence on entrepreneurial intentions. The gender variable moderates the influence of entrepreneurial education on entrepreneurial intentions. The gender variable moderates the influence of entrepreneurial self-confidence on entrepreneurial intentions.Keywords: Entrepreneurship education, entrepreneurial self-efficacy, entrepreneurial intention, gender